LES SOCIÉTÉS HUMAINES FACE AUX CHANGEMENTS CLIMATIQUES Volume 2 La protohistoire, des débuts de l'Holocène au début des temps historiques - Djindjian, François (2023)
The two volumes bring together the contributions of the members of the International Union of Prehistoric and Protohistoric Sciences (UISPP), to a project launched in 2017, with the support of the International Academic Union (UAI), under the title Human societies facing climate change in prehistory and protohistory : from the origins of Humanity to the beginning of historical times. The second volume concerns protohistory, from the beginning of the Holocene to historical times. In what climate and at what latitudes have the innovations represented by farming and animal husbandry succeeded in sustaining themselves? How did agro-pastoral societies adapt to the progression of Holocene aridity after the exceptional wet period at its beginning? Is nomadic pastoralism a specialization of an agro-pastoral society in the context of increasing aridity and/or an adaptation of animal domestication to steppe and semi-desert areas? How have agro-pastoral societies adapted to multi-century periods of climate change such as those known from protohistoric and historical periods (the crises of 8200 BP, 4200 BP, 1200 BC and 800 BC; the Roman climate optimum; the crisis of the Later Roman Empire and barbarian invasions; the medieval climate optimum; the Little Ice Age)? And how did they survive episodes of adverse weather lasting several years that caused scarcity and famine?